Wiley encyclopedia of operations research and management science - Cochran, James J.; Cox, Louis A. (Hoboken, N.J. : Wiley, 2011)
'This multi-volume encyclopedia is organized alphabetically and contains four levels of articles (Introductory, Advanced, Technical, and Case Studies/Historical Interludes) designed to make its content useful and accessible to the widest possible readership.Introductory articles provide a broad and moderately technical treatment of core topics at a level suitable for advanced undergraduate students as well as scientists without a strong background in the field. Advanced articles, aimed at graduate students and researchers, review key areas of research in a citation-rich format similar to that of leading review journals. Technical articles, written as'breakouts' from the advanced articles, provide more detailed discussions of key concepts addressed in the reviews.Case studies/biographical sketches/historical interludes provide an opportunity to present successful and/or interesting examples of operations research/management science methodology in practice or in historical contexts. These articles are less technical in nature and aimed primarily at graduate students and practicing researchers. EORMS has also been developed as a dynamic online resource, combining the most useful features of traditional reference works and review journals in a compelling format designed to exploit the full potential of the online medium. Extensive linking to the primary literature and to other online resources such as the Wiley Encyclopedia of Statistical Sciences, Second Edition further enhances the value of EORMS as a gateway to broader scientific literature. The editorial approach and structure of EORMS ensures the longevity of its content'--
'This multi-volume encyclopedia is organized alphabetically and contains four levels of articles (Introductory, Advanced, Technical, and Case Studies/Historical Interludes) designed to make its content useful and accessible to the widest possible readership. Introductory articles provide a broad and moderately technical treatment of core topics at a level suitable for advanced undergraduate students as well as scientists without a strong background in the field. Advanced articles, aimed at graduate students and researchers, review key areas of research in a citation-rich format similar to that of leading review journals. Technical articles, written as'breakouts' from the advanced articles, provide more detailed discussions of key concepts addressed in the reviews. Case studies/biographical sketches/historical interludes provide an opportunity to present successful and/or interesting examples of operations research/management science methodology in practice or in historical contexts. These articles are less technical in nature and aimed primarily at graduate students and practicing researchers'--
V. 1. A-Co -- v. 2. Co-Dy -- v. 3. Dy-Im -- v. 4. Im-Ma -- v. 5. Ma-Op -- v. 6. Op-Re -- v. 7. Re-Su -- v. 8. Ru-W; index.
Includes bibliographical references and index.
Keywords: Operations research -- Encyclopedias